Apport du portfolio numérique d'apprentissage et de la vidéo pour l'autoévaluation de la compétence en production orale d'élèves du secondaire en classe de français, langue d'enseignement - Maxime Paquet; Thierry Karsenti (ALSIC: Apprentissage des Langues et Systèmes d'Information et de Communication)
This study starts with the observation that we do not know much about the use of eportfolios and self-evaluation actions in an oral production learning context. From this observation arises our theoretical framework, elaborated around oral didactical models (Dumais, 2010a; Lafontaine, 2007) and empirical data regarding the use of eportfolios and self-evaluation, upon which we wish to bring new data thanks to our research, which carries the goal of describing and analysing the benefit of eportfolios to the self-evaluation capacity in the secondary school students' oral proficiency. In order to reach this goal, we analyzed overall self-evaluations contained in eportfolios and the responses of two questionnaires filled by 77 students in the third year of secondary school (N=77) and in a more specific manner, we analyzed 16 of these students' self-evaluation content (N=16) who also participated in an individual interview. Our data collection allowed us to describe in which way the use of eportfolios improved the students' self-evaluation capacity.